2007
DOI: 10.1016/j.resuscitation.2006.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Drug administration in animal studies of cardiac arrest does not reflect human clinical experience

Abstract: Introduction-To date, there is no evidence showing a benefit from any advanced cardiac life support (ACLS) medication in out-of-hospital cardiac arrest (OOHCA), despite animal data to the contrary. One explanation may be a difference in the time to first drug administration. Our previous work has shown the mean time to first drug administration in clinical trials is 19.4 minutes. We hypothesized that the average time to drug administration in large animal experiments occurs earlier than in OOHCA clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 135 publications
1
40
0
Order By: Relevance
“…It was demonstrated in our group that chest compressions with the LUCAS device during experimental resuscitation resulted in higher cerebral blood flow and cardiac output than standard manual external chest compressions [165]. In animal studies, superior survival rates with drugs have been demonstrated in comparison with humans, probably due to the fact that drug administration occurs some 10 min earlier in humans than in animal studies [166]. Shorter drug delivery time in animal models of CA may thus be one reason for the failure of animal studies to translate successfully into the clinical arena [16,166].…”
Section: The Experimental Model Of Cprmentioning
confidence: 87%
See 1 more Smart Citation
“…It was demonstrated in our group that chest compressions with the LUCAS device during experimental resuscitation resulted in higher cerebral blood flow and cardiac output than standard manual external chest compressions [165]. In animal studies, superior survival rates with drugs have been demonstrated in comparison with humans, probably due to the fact that drug administration occurs some 10 min earlier in humans than in animal studies [166]. Shorter drug delivery time in animal models of CA may thus be one reason for the failure of animal studies to translate successfully into the clinical arena [16,166].…”
Section: The Experimental Model Of Cprmentioning
confidence: 87%
“…In animal studies, superior survival rates with drugs have been demonstrated in comparison with humans, probably due to the fact that drug administration occurs some 10 min earlier in humans than in animal studies [166]. Shorter drug delivery time in animal models of CA may thus be one reason for the failure of animal studies to translate successfully into the clinical arena [16,166]. Using a swine model, it was demonstrated that the duration of resuscitation may be extended throughout the use of a vasoactive drug prior to rescue countershock [167].…”
Section: The Experimental Model Of Cprmentioning
confidence: 99%
“…(27,28) Based on available literature, the mean time to first drug administration was only 9.5 min in experiments while in the out-ofhospital setting, the first drug is usually given 19.4 minutes after suspected onset of VF. (27) Thus, the flowchart of our study was designed to respect realistic timing of OHCA. (27) …”
Section: Discussionmentioning
confidence: 99%
“…This is significantly longer than administration times in animal studies where drugs are frequently given in under 10 min [77][78][79]. Reynolds et al found a mean time of 9.5 min to first drug administration in animal CPR models compared with the 19.4 min reported in human clinical trials [80].…”
Section: Intraosseous Administration Of Epinephrinementioning
confidence: 98%